Response of tow varieties of okra (Abelmoschus esculentus L. Moench) to application methods of humic acid, zolfast and their effects on vegetative growth charectristics and yield - A. A. Yaseen; N. S. A. Al-Mousawy (Al-Qadisiyah Journal of Pure Science, 2017)
The experiment was conducted in Agriculture College, University of AL–Qadisiya during the period of 10/4/2011 till 15/10/2011. The aim of the study was studying response of two okra cultivars (Al–Husenawyia and Al–Pteira), humic acid and zolfast application methods (foliar and addition to irrigation water) and this concentration (recommended and doubled) on vegetative growth charectristics and yieldThe humic acid and zolfast formulas were added twice by the use of hand sprayer. The recommended concentration for humic acid and zolfast as foliar spraying were 1 ml.L-1 and 2 ml.L-1 if doubled respectively while when used with irrigation water 4.8 ml.L-1 and 9.6 ml.L-1 at double for humic acid 7.2 and 14.4 ml.L-1 for zolfast if doubled.The design of the experiment was Randomized Complete Blocks in a factorial arrangement (2×2×5) in three replications. The RLSD at 0.05 was used as a method of mean separation treatment effect was evident.The results showed:1- Al–Husenawyia cultivar was superior in specific leaf weight, relative growth rate, vegetative dry weight, root dry weight, fruit length, number of fruit/plant, fruits yield compared to Al–Pteira had higher fruit dry weights.2- Foliar application method of humic acid and zolfast showed beneficial effect on all parameters studies except root dry weight.3- No significant difference were found between the recommended concentrations of humic acid or zolfast in, relative growth rate, vegetative dry weight, root dry weight, fruit length, fruit dry weight, number of fruit/plant.4- The interaction between cultivars and humic acid and zolfast concentrations revealed that both cultivars had different response to the applied concentrations of humic and zolfast. Al–Husenawyia had higher relative growth rate, vegetative dry weight, and root dry weight. While Al–Pteira had higher specific leaf weight when used the double recommended concentration of zolfast.5- The three way interaction factors studied in the experiment revealed an increase in growth parameter of both cultivars when humic acid and zolfast were added in their higher concentration (double recommended) by foliar application expect root dry weight which were increased when added to the irrigation water. Al–Husenawyia cultivar was higher in all parameters with the use of higher concentration of humic acid and zolfast when applied with irrigation water or foliar application. The three way interaction revealed no significant difference in vegetative dry weight, fruit dry weight.